Foreign Language Anxiety: A Study on Spanish Learners - Akter, Moumita (International Journal of Language and Literary Studies, 2024)
Foreign language anxiety (FLA) as a crucial affective variable has been unexplored in the context of the Spanish language. This paper reports a study that investigated Spanish language anxiety (SLA) and its potential causes and inquired into the relationship between the role of a teacher and SLA. A mixed-methods research design was adopted, including a questionnaire [Foreign Language Classroom Anxiety Scale (FLCAS)], semi-structured interviews, and observation as data collection among the undergraduates (female = 32, male = 18) and Spanish teachers (2). The FLCAS data revealed that students experience low to moderate anxiety, with communication apprehension being highly rated (mean = 3.26) followed by fear of negative evaluation (mean = 2.8) and test anxiety (mean = 2.25). The interview data recorded listening and speaking tasks, fear of negative evaluation, teacher talk, negative self-comparison, and previous bad language learning experiences are the prominent sources of anxiety. In this context, Spanish teachers are found to reduce students’ anxiety mostly by giving interesting activities, accepting students’ mistakes, and using body language. This paper offers insight into the causes that trigger FLA and an impactful relationship between a teacher’s role and FLA. Some suggestions are proposed for teachers based on the findings to mitigate students’ anxiety.